2010
DOI: 10.1111/j.1365-2486.2010.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Warmer and richer? Predicting the impact of climate warming on species richness in small temperate waterbodies

Abstract: Climate change is expected to affect communities worldwide. Many studies focus on responses at the regional level and show an increase in species richness. However, less is known about the consequences of climate change at the local scale (in ecosystems). Small waterbodies, such as ponds, could play an important role for the assessment of the impact of future changes in climate at the local level. We evaluated here the potential changes due to climate warming in the species richness for various groups (plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 64 publications
3
54
1
2
Order By: Relevance
“…However, evidence for an effect of connectivity at smaller spatial scales is equivocal . In an analysis of climatic correlates of ponds varying in altitude, Rosset et al (2010) found that environmental temperature explained a large proportion of the variance in species richness. Rosset et al argue that there could be a 83% increase in species richness in lowland areas and a 150% increase in species richness in upland areas under projected climate warming.…”
Section: Physical Correlates Of Pond Species Richnessmentioning
confidence: 99%
“…However, evidence for an effect of connectivity at smaller spatial scales is equivocal . In an analysis of climatic correlates of ponds varying in altitude, Rosset et al (2010) found that environmental temperature explained a large proportion of the variance in species richness. Rosset et al argue that there could be a 83% increase in species richness in lowland areas and a 150% increase in species richness in upland areas under projected climate warming.…”
Section: Physical Correlates Of Pond Species Richnessmentioning
confidence: 99%
“…The variations that occur in the species composition and distribution of certain species of aquatic macrophytes, mostly submerged ones due to thermal changes, indicate that temperature is as important as light in influencing competitive interactions among coexisting species (Anderson 1969;Allen and Gorham 1973;Barko et al 1986). Recent studies have found that the increased nutrient concentrations, derived from diffuse pollution due to increased precipitation in future can hinder temperature driven distribution changes of macrophytes (Jylha et al 2004;Rosset et al 2010). …”
Section: Temperaturementioning
confidence: 99%
“…Several studies have established that the nutrient enrichment can cause significant changes in the density, species composition and richness of aquatic vegetation in lakes (Toivonen and Huttunen 1995;Findlay and Houlahan 1997;Bini et al 1999;Magee et al 1999;Lougheed et al 2001;Rosset et al 2010;Alahuhta 2011). There is a possibility that the elevated nutrient concentrations might hamper climate-driven distribution patterns of macrophytes (Rosset et al 2010). Nutrient enrichment of waters due to clay soils probably resulted in a positive relationship between helophyte vegetation distribution and fi-Factors affecting the distribution patterns of aquatic macrophytes ner grained soils and less acidic bedrocks.…”
Section: Nutrient Enrichmentmentioning
confidence: 99%
“…Both large-scale land cover alterations and an increasing mobility of humans have resulted in the homogenization of the earth's fauna and flora in many anthropogenic regions (McKinney, 2006). In addition, anthropogenically induced climate change can cause geographical range changes and altitudinal shifts in floral and faunal distribution, contributing to biotic homogenization particularly in biodiversity hotspots (Thuiller, 2007;Rosset et al, 2010). Human introductions (accidental and deliberate) of non-native taxa have promoted the proliferation of generalist, opportunistic species at the expense of specialized, sensitive taxa in many instances.…”
Section: Biodiversity Lossmentioning
confidence: 99%